Monetary policy and financial stability in emerging market economies - Martin Tobal; Lorenzo Menna (Latin American Journal of Central Banking (LAJCB), 2020)
During the 1990s and early 2000s, the consensus was that central banks had to adjust interest rates only in response to inflation and (possibly) output. Such consensus was questioned in the aftermath of the Global Financial Crisis, as well as during the present pandemic. In contrast with most of the traditional literature, some observers argued that financial crises are endogenous events, claiming that central banks also had to dampen the accumulation of financial imbalances; that is, they had to "lean against the wind." However, this debate has, for the most part, focused on advanced economies (AEs), overlooking important characteristics of emerging market economies (EMEs). Based on more recent literature, in this paper, we set the terms of the debate for EMEs. We argue that the relationship between monetary policy and financial stability is different in these economies because, unlike in AEs, the financial conditions are strongly dependent on capital flows. This characteristic of EMEs makes the trade-offs faced by their central banks more complex.
Keywords: E58; E44; 330; Capital flows; Financial crisis; Leaning against the wind